A high-tenacity breathable nylon staple fiber and its testing process
By designing a hollow multi-leaf structure and uniformly distributed through holes in nylon staple fibers, combined with the interface compatibilizer treatment, the problem of insufficient breathability of existing nylon staple fibers is solved, high breathability and toughness are achieved, production costs are reduced, and it is suitable for high-performance textiles.
Patent Information
- Application Number
- CN202411922519.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing nylon staple fibers have shortcomings in breathability, and the multi-layer structure of composite design is complex, which increases production costs and is not conducive to large-scale promotion and application.
By designing a hollow multi-leaf structure and uniformly distributing radial through holes in the sheath layer, combined with the interface compatibilizer treatment, the breathability and toughness of nylon staple fibers are improved, and raw material costs and resource waste are reduced.
It significantly improves the breathability and toughness of nylon staple fiber, optimizes hygroscopicity and moisture permeability, reduces production costs, and is suitable for high-performance textiles.
Smart Images

Figure CN119777009A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber material testing, and in particular to a high-tenacity breathable nylon staple fiber and a testing process thereof. Background Art
[0002] Nylon staple fiber is a fiber material with excellent comprehensive performance. Although traditional nylon staple fiber has good strength and wear resistance, it is insufficient in air permeability. Although some progress has been made in the prior art for improving nylon staple fiber, for example, the patent application with publication number: CN207825612U discloses a functional nylon staple fiber, including a surface layer, an intermediate layer, a transition layer and a bottom layer, the intermediate layer is located between the surface layer and the bottom layer, the number of the transition layers is two: transition layer one and transition layer two, the transition layer one is located between the surface layer and the intermediate layer, the transition layer two is located between the intermediate layer and the bottom layer, the surface layer is made of polyester material, the intermediate layer is made of linen material, and the bottom layer is made of cotton material, the transition layer one has a plurality of concave functional notches, the surface layer is partially embedded in the functional notches, the transition layer two has a plurality of through holes, and the through holes have a connector for firmly connecting the intermediate layer to the bottom layer.
[0003] Although the above patent solves the problem of poor stability in the prior art, the composite design in the prior art increases the complexity of the microstructure. However, due to problems such as uneven distribution of through holes and interlayer barrier effect, the overall air permeability is only limitedly improved. The preparation of the multi-layer structure requires complex processing technology, and the use of multiple materials increases production costs, which is not conducive to large-scale promotion and application. Summary of the invention
[0004] The purpose of the present invention is to provide a high-toughness breathable nylon staple fiber and a testing process thereof. Through the design of a hollow multi-lobate structure, not only the breathability is improved, but also the amount of nylon material used is reduced, thereby reducing the cost of raw materials and resource waste; at the same time, based on structural optimization and surface modification, the nylon staple fiber of the present invention can be further expanded to the field of multifunctional textiles such as antibacterial and flame retardant to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A high-tenacity, breathable nylon staple fiber comprises a core layer and a sheath layer, wherein the sheath layer wraps the core layer inside, the sheath layer is provided with through holes evenly distributed along the radial direction, the core layer and the sheath layer are bonded by an interface bulking agent to form a core-sheath bonding interface, the cross-section of the nylon staple fiber is a hollow multi-lobal structure, the hollow rate of the hollow multi-lobal structure is 10%-30%, and the number of multi-lobal blades is 8.
[0007] Furthermore, the nylon staple fiber is prepared by high-speed spinning and high-speed stretching deformation process, wherein the spinning speed is not less than 4000m / min, the stretching ratio is 1:3-1:5, the heat setting temperature is controlled in the range of 180℃-220℃, and the prepared fiber surface is coated and smoothed to obtain high-toughness breathable nylon staple fiber.
[0008] Furthermore, the obtained high-toughness breathable nylon staple fiber has a tensile strength greater than 6.0 cN / dtex; an elongation at break of 20%-40%; and an air permeability of not less than 20m 3 / h·m 2 , hygroscopicity is 4%-8%.
[0009] The present invention provides another technical solution, a testing process for high-tenacity breathable nylon staple fibers, comprising the following steps:
[0010] Step 1: Performance test: Perform a tensile test on the nylon staple fiber to measure its breaking strength and elongation, use an air permeability tester to measure the air permeability of the nylon staple fiber, and use a moisture vapor transmission rate tester to test the moisture permeability of the nylon staple fiber;
[0011] Step 2: Surface structure analysis: Scan and observe the surface structure of nylon staple fibers, analyze the surface morphology and microstructure of nylon staple fibers, and verify the air permeability and structural characteristics of nylon staple fibers that enhance their toughness;
[0012] Step 3: Fiber fineness measurement: Measure the fineness of the nylon staple fiber, weigh and calculate the diameter and surface characteristics of the nylon staple fiber to ensure that the diameter of the nylon staple fiber is within the range of 1-10μm;
[0013] Step 4: Wear resistance test: The wear resistance of the staple fiber is tested based on a friction and wear tester. The staple fiber sample is rubbed with a specific material, the surface loss and deformation are measured, and the durability and long-term effectiveness of the nylon staple fiber in practical applications are evaluated.
[0014] Furthermore, the performance test specifically includes:
[0015] Mechanical properties test:
[0016] Ten nylon staple fibers were randomly selected from the same batch of high-tenacity breathable nylon staple fibers as test samples. The tensile strength of each test sample was tested using an electronic single-fiber tensile machine to determine the maximum tensile force and tensile breaking point of the test sample.
[0017] The tensile modulus and elongation at break of the test sample are calculated based on the maximum tensile force and tensile breaking point, and the tensile properties of nylon staple fibers are evaluated by comparing the calculated results with the predetermined mechanical properties.
[0018] Among them, the stretching speed of the electronic single fiber stretching machine is 500mm / min, the test temperature is 23℃, and the relative humidity is 65%;
[0019] Air permeability test:
[0020] The nylon staple fiber samples were pressed into fiber layers according to the specified thickness and density, and the air flow through the fiber layers was measured using an air permeability tester. The air permeability of the nylon staple fiber samples was evaluated based on the measurement results.
[0021] The air permeability tester measures the amount of gas passing through the nylon staple fiber sample within a certain period of time under a constant airflow, and the unit of gas volume is m 3 / h*m 2 .
[0022] Furthermore, the air permeability test also includes:
[0023] Moisture vapor transmission rate test:
[0024] Under constant temperature and humidity conditions, place the nylon staple fiber sample in a dryer and record the initial mass of the nylon staple fiber sample;
[0025] Expose the nylon staple fiber sample to an environment with a relative humidity of 65% for 12 hours, and record the mass of the nylon staple fiber sample after moisture absorption;
[0026] The moisture absorption rate was calculated based on the initial mass and the mass after moisture absorption, that is, the moisture absorption was the percentage of the difference between the mass after moisture absorption and the initial mass. At the same time, the speed at which water vapor permeated through the nylon staple fiber sample was tested;
[0027] The suitability of nylon staple fiber samples was evaluated based on the moisture absorption rate and the speed at which water vapor permeates through the nylon staple fiber samples.
[0028] Furthermore, the surface structure analysis includes:
[0029] Microscopic morphology analysis:
[0030] The surface of nylon staple fibers was scanned by electron microscope to observe the microporous structure distribution, pore morphology and cross-sectional characteristics of the core-sheath bonding interface on the surface of nylon staple fibers;
[0031] Verify the uniformity and microscopic bonding strength of the core-sheath interface, analyze the number, distribution pattern and hollow ratio of the leaves in the hollow multi-leaf structure, and confirm whether the nylon staple fiber meets the design requirements;
[0032] Micropore Characterization Evaluation:
[0033] Determine the specific surface area and porosity of nylon staple fibers, record the pore size range and distribution frequency of the microporous structure, and verify whether the microporous structure is within the range of 1-10nm;
[0034] The total amount of microporous structure was counted, and based on the statistical results and the fiber cross-sectional morphology, the contribution of the microporous structure to the air permeability was evaluated.
[0035] Furthermore, the surface structure analysis also includes:
[0036] Surface energy determination:
[0037] Based on the contact angle test method, the contact angle of water droplets on the surface of nylon staple fibers was measured, the surface energy parameters were calculated, and the polar component and dispersion component of the surface energy were decomposed;
[0038] The dynamic changes of surface energy of nylon staple fibers treated with hydrophilic modifiers were analyzed to evaluate the modification effect of hydrophilic modifiers on surface hygroscopicity.
[0039] Test the effect of different temperature and humidity conditions on the moisture absorption performance of the fiber surface, and evaluate the ability of nylon staple fibers to maintain hydrophilicity in long-term use environments;
[0040] Combined with the surface energy parameters, verify whether the nylon staple fiber meets the technical requirements for enhanced moisture permeability and moisture absorption, and record the uniformity of the modifier distribution and the depth of action;
[0041] Coating distribution analysis:
[0042] Conduct layered observations on nylon staple fiber coatings, analyze the consistency of coating thickness and fiber surface coverage, and verify the adhesion performance of hydrophilic coating materials;
[0043] Observe the microstructure of the nylon staple fiber coating, use microscope imaging technology to confirm whether the coating completely covers the fiber surface, and record the compatibility of the coating with the microporous structure;
[0044] Test the adhesion of coating materials, evaluate the durability of coatings through multiple friction tests, and record the coating shedding rate and surface wear;
[0045] The effect of coating on the surface friction coefficient of nylon staple fibers was analyzed to verify whether coating treatment reduces friction and enhances the wear resistance of the fibers.
[0046] Furthermore, the surface loss and deformation are measured in step 4, specifically including:
[0047] Obtain the mass data of the nylon staple fiber samples before and after the friction test, and calculate the mass loss rate based on the initial mass and the mass after friction;
[0048] Scan the surface of nylon staple fiber through an electron microscope, record the surface morphology data of nylon staple fiber sample before and after friction, and at the same time, record the depth, width and distribution characteristics of damage marks;
[0049] The depth deformation, width expansion and surface roughness change of the friction area of nylon staple fiber samples were measured, and the deformation degree of the samples was analyzed by combining the three-dimensional surface profile map. The ratio of the deformation loss area to the initial surface area was calculated to quantify the surface deformation loss rate.
[0050] Compare the damage morphology under different friction conditions, analyze the wear resistance of the nylon staple fiber surface coating, detect surface cracks, shedding and other damage characteristics, and evaluate the impact of friction on the durability of nylon staple fibers;
[0051] According to the loss test results under different friction conditions, the relationship curve between friction loss rate and friction times was drawn to analyze the time series change of short fiber loss rate;
[0052] If the test finds that the loss rate of the short fiber sample during the friction process exceeds the preset rate threshold, the friction and wear tester will trigger an abnormal alarm, analyze the microscopic characteristics of the abnormal loss area, and confirm the cause of the fault in combination with the scanning data.
[0053] Furthermore, it also includes comprehensive analysis and evaluation of the test data, including:
[0054] Based on the time series data of each test result, the performance characteristic curve of nylon staple fiber is drawn, and the time series change trend of mechanical properties, air permeability and wear resistance of nylon staple fiber is analyzed;
[0055] Combine the performance characteristic curve data to conduct multi-dimensional evaluation of various test indicators, and extract key characteristic parameters based on the evaluation results;
[0056] Calculate the comprehensive evaluation score of each test indicator according to the preset weight formula based on the test results;
[0057] The tensile strength, elongation at break, air permeability, moisture permeability and abrasion resistance scores are weighted and summed to obtain the overall performance evaluation score of nylon staple fiber;
[0058] Judging whether the nylon staple fiber meets the requirements of high toughness and air permeability indexes according to the overall performance score of the nylon staple fiber;
[0059] If the evaluation result is lower than the preset standard, optimization suggestions will be output and improvements and adjustments will be made to the corresponding performance indicators. If the evaluation result meets the preset standard, testing and certification will be passed to confirm that the nylon staple fiber is suitable for the field of high-performance textiles.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] By evenly distributing radial through holes in the sheath layer and designing a hollow multi-lobate structure, the air circulation channel of the nylon staple fiber is effectively increased, and the air permeability of the fiber is improved. The core-sheath bonding structure and the interface compatibilizer treatment significantly improve the bonding strength of the core-sheath interface of the nylon staple fiber, so that the staple fiber has excellent tensile strength and elongation at break, ensuring its high toughness and stability in use, and optimizing its moisture absorption and moisture permeability. Through the optimized wear resistance test and evaluation method, it is verified that the surface loss and deformation of the nylon staple fiber under friction conditions are at a low level, and the surface coating shows excellent adhesion and durability. The comprehensive performance evaluation system provides a scientific basis for the comprehensive evaluation of the performance of nylon staple fibers, and can efficiently screen out staple fiber products that meet high performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a cross-sectional view of the chemical structure of the high-toughness breathable nylon staple fiber of the present invention;
[0063] Figure 2 This is a schematic diagram of the cross-sectional structure of the high-toughness breathable nylon staple fiber of the present invention;
[0064] Figure 3 This is a test process flow chart of the high-toughness breathable nylon staple fiber of the present invention;
[0065] In the figure: 1, core layer; 2, sheath layer; 21, through hole; 3, core-sheath bonding interface. DETAILED DESCRIPTION
[0066] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0067] In order to solve the technical problems that the composite design in the prior art increases the complexity of the microstructure, but due to the uneven distribution of through holes and the barrier effect between layers, the overall air permeability is limited, the preparation of the multi-layer structure requires complex processing technology, and the use of multiple materials increases the production cost, which is not conducive to large-scale promotion and application, please refer to Figure 1-Figure 2 , this embodiment provides the following technical solutions:
[0068] A high-toughness breathable nylon staple fiber comprises a core layer 1 and a sheath layer 2, wherein the core layer 1 is made of a high-crystallinity polyamide material, the main chain molecular weight of the polyamide is 10000-15000, the amide bond ratio is greater than 40%, and the fiber is used to provide mechanical strength and durability; the sheath layer 2 is made of a low-crystallinity polyamide material with a microporous structure, the microporous structure has a pore size of 1-10 nm, a porosity of 20%-40%, and is modified by a hydrophilic modifier to improve hygroscopicity and air permeability; the sheath layer 2 wraps the core layer 1 inside thereof, and the sheath layer 2 is provided with through holes 21 uniformly distributed along the radial direction; the core layer 1 and the sheath layer 2 are combined by an interface compatibilizer to form a core-sheath bonding interface 3; the cross section of the nylon staple fiber is a hollow multi-lobed structure, the hollow rate of the hollow multi-lobed structure is 10%-30%, and the number of multi-lobed leaves is 8, so as to increase the specific surface area and air permeability.
[0069] In this embodiment, the capacity expansion technology of the core-sheath structure bonding interface 3 realizes a multi-level composite structure design. The interface expander can enhance the bonding force between the core layer 1 and the sheath layer 2 to form a high-strength core-sheath bonding interface 3, and transfer the external force from the sheath layer 2 to the core layer 1, or from the core layer 1 to the sheath layer 2, so that the staple fibers can be evenly stressed and the nylon staple fibers can withstand external forces, thereby improving the comprehensive performance of the nylon staple fibers and ensuring the overall performance of the nylon staple fibers. The sheath layer 2 adopts microporous and hydrophilic modification to enhance air permeability and comfort, and the hollow multi-leaf cross-section design further achieves higher air permeability and lightweight characteristics through shape optimization.
[0070] In this embodiment, the nylon staple fiber is prepared by high-speed spinning and high-speed stretching deformation process, wherein the core layer 1 has a high crystallinity region, and its crystallinity is not less than 50%, so as to achieve a high degree of orientation of the molecular chain, wherein the spinning speed is not less than 4000m / min, the stretching ratio is 1:3-1:5, and the heat setting temperature is controlled in the range of 180℃-220℃ to achieve a high degree of orientation and crystallization of the molecular chain, and the prepared fiber surface is coated and smoothed to obtain a high-toughness breathable nylon staple fiber, and the obtained high-toughness breathable nylon staple fiber has a tensile strength greater than 6.0cN / dtex; an elongation at break of 20%-40%; and the air permeability of the nylon staple fiber is not less than 20m 3 / h·m 2 The hygroscopicity is 4%-8%. The coating includes polyethylene glycol or polyether ester material to further enhance the hygroscopicity and air permeability. The fiber surface is smoothed to reduce the friction coefficient and improve the wear resistance.
[0071] In order to better achieve high tenacity breathable nylon staple fiber, please refer to Figure 3 The present invention provides a testing process for high-toughness breathable nylon staple fibers, comprising the following steps:
[0072] Step 1: Performance test: Perform a tensile test on the nylon staple fiber to measure its breaking strength and elongation, use an air permeability tester to measure the air permeability of the nylon staple fiber, and use a moisture vapor transmission rate tester to test the moisture permeability of the nylon staple fiber;
[0073] Step 2: Surface structure analysis: Scan and observe the surface structure of nylon staple fibers, analyze the surface morphology and microstructure of nylon staple fibers, and verify the air permeability and structural characteristics of nylon staple fibers that enhance their toughness;
[0074] Step 3: Fiber fineness measurement: Measure the fineness of the nylon staple fiber, weigh and calculate the diameter and surface characteristics of the nylon staple fiber to ensure that the diameter of the nylon staple fiber is within the range of 1-10μm, meeting the requirements of high toughness and air permeability;
[0075] Step 4: Abrasion resistance test: The abrasion resistance of the staple fiber is tested by using a friction and wear tester. The staple fiber sample is rubbed against a specific material to measure the surface loss and deformation, and to evaluate the durability and long-term effectiveness of the nylon staple fiber in practical applications.
[0076] In this embodiment, the test data is also comprehensively analyzed and evaluated, including:
[0077] Based on the time series data of each test result, the performance characteristic curve of nylon staple fiber is drawn, and the time series change trend of mechanical properties, air permeability and wear resistance of nylon staple fiber is analyzed;
[0078] Combine the performance characteristic curve data to conduct multi-dimensional evaluation of various test indicators, and extract key characteristic parameters based on the evaluation results;
[0079] Calculate the comprehensive evaluation score of each test indicator according to the preset weight formula based on the test results;
[0080] The tensile strength, elongation at break, air permeability, moisture permeability and abrasion resistance scores are weighted and summed to obtain the overall performance evaluation score of nylon staple fiber;
[0081] Judging whether the nylon staple fiber meets the requirements of high toughness and air permeability indexes according to the overall performance score of the nylon staple fiber;
[0082] If the evaluation result is lower than the preset standard, optimization suggestions will be output and improvements and adjustments will be made to the corresponding performance indicators. If the evaluation result meets the preset standard, testing and certification will be passed to confirm that the nylon staple fiber is suitable for the field of high-performance textiles.
[0083] In this embodiment, the mechanical properties, air permeability, moisture permeability and wear resistance of nylon staple fibers are comprehensively evaluated by systematic performance testing, surface structure analysis, fiber fineness measurement and wear resistance testing. By drawing performance characteristic curves and multi-dimensional evaluation, extracting key characteristic parameters, and calculating comprehensive evaluation scores, it is finally determined whether the nylon staple fibers meet the requirements of high toughness and air permeability indicators, which not only ensures the quality and performance of nylon staple fibers, but also provides optimization suggestions for deficiencies, so that nylon staple fibers have better durability, long-term effect and comfort when used in the field of high-performance textiles, thereby significantly improving the market competitiveness of the products.
[0084] In this embodiment, the performance test specifically includes:
[0085] Mechanical properties test:
[0086] Ten nylon staple fibers were randomly selected from the same batch of high-tenacity breathable nylon staple fibers as test samples. The tensile strength of each test sample was tested using an electronic single-fiber tensile machine to determine the maximum tensile force and tensile breaking point of the test sample.
[0087] The tensile modulus and elongation at break of the test sample are calculated based on the maximum tensile force and tensile breaking point, and the tensile properties of nylon staple fibers are evaluated by comparing the calculated results with the predetermined mechanical properties.
[0088] Among them, the stretching speed of the electronic single fiber stretching machine is 500mm / min, the test temperature is 23℃, and the relative humidity is 65%;
[0089] Air permeability test:
[0090] The nylon staple fiber samples were pressed into fiber layers according to the specified thickness and density, and the air flow through the fiber layers was measured using an air permeability tester. The air permeability of the nylon staple fiber samples was evaluated based on the measurement results.
[0091] The air permeability tester measures the amount of gas passing through the nylon staple fiber sample within a certain period of time under a constant airflow, and the unit of gas volume is m 3 / h*m 2 .
[0092] In this embodiment, the air permeability test further includes:
[0093] Moisture vapor transmission rate test:
[0094] Under constant temperature and humidity conditions (23°C, relative humidity 65%), place the nylon staple fiber sample in a dryer and record the initial mass of the nylon staple fiber sample;
[0095] Expose the nylon staple fiber sample to an environment with a relative humidity of 65% for 12 hours, and record the mass of the nylon staple fiber sample after moisture absorption;
[0096] The moisture absorption rate was calculated based on the initial mass and the mass after moisture absorption, that is, the moisture absorption was the percentage of the difference between the mass after moisture absorption and the initial mass. At the same time, the speed at which water vapor permeated through the nylon staple fiber sample was tested;
[0097] The suitability of nylon staple fiber samples was evaluated based on moisture absorption and the rate at which water vapor permeates through the nylon staple fiber samples to determine their suitability for applications that require high breathability, such as keeping the skin dry.
[0098] In this embodiment, by conducting mechanical property tests and air permeability tests on high-tenacity breathable nylon staple fibers, the excellent performance of the nylon staple fibers in mechanics and air permeability is ensured. At the same time, the combination of the air permeability test and the moisture vapor permeability test effectively evaluates the air permeability and moisture absorption and perspiration capacity of the nylon staple fibers, so that the nylon staple fibers perform well in keeping the skin dry and comfortable, which not only improves the quality and reliability of nylon staple fiber products, but also provides strong technical support for their application in the field of high-performance textiles, thereby bringing better user experience and market recognition.
[0099] In this embodiment, the surface structure analysis includes:
[0100] Microscopic morphology analysis:
[0101] The surface of the nylon staple fiber was scanned by an electron microscope to observe the microporous structure distribution, pore morphology and cross-sectional characteristics of the core-sheath bonding interface 3 on the surface of the nylon staple fiber;
[0102] Verify the uniformity and microscopic bonding force of the core-sheath bonding interface 3, analyze the number, distribution pattern and hollow ratio of the leaves in the hollow multi-leaf structure, and confirm whether the nylon staple fiber meets the design requirements;
[0103] Micropore Characterization Evaluation:
[0104] Determine the specific surface area and porosity of nylon staple fibers, record the pore size range and distribution frequency of the microporous structure, and verify whether the microporous structure is within the range of 1-10nm;
[0105] The total amount of microporous structure is counted, and based on the statistical results and the fiber cross-sectional morphology, the contribution of microporous structure to air permeability is evaluated;
[0106] Surface energy determination:
[0107] Based on the contact angle test method, the contact angle of water droplets (including water and glycerin) on the surface of nylon staple fibers is measured, the surface energy parameters are calculated, and the polar component and dispersion component of the surface energy are decomposed;
[0108] The dynamic changes of surface energy of nylon staple fibers treated with hydrophilic modifiers were analyzed to evaluate the modification effect of hydrophilic modifiers on surface hygroscopicity.
[0109] Test the effect of different temperature and humidity conditions on the moisture absorption performance of the fiber surface, and evaluate the ability of nylon staple fibers to maintain hydrophilicity in long-term use environments;
[0110] Combined with the surface energy parameters, verify whether the nylon staple fiber meets the technical requirements for enhanced moisture permeability and moisture absorption, and record the uniformity of the modifier distribution and the depth of action;
[0111] Coating distribution analysis:
[0112] Conduct layered observations on nylon staple fiber coatings, analyze the consistency of coating thickness and fiber surface coverage, and verify the adhesion performance of hydrophilic coating materials;
[0113] Observe the microstructure of the nylon staple fiber coating, use microscope imaging technology to confirm whether the coating completely covers the fiber surface, and record the compatibility of the coating with the microporous structure;
[0114] Test the adhesion of coating materials, evaluate the durability of coatings through multiple friction tests, and record the coating shedding rate and surface wear;
[0115] The effect of coating on the surface friction coefficient of nylon staple fibers was analyzed to verify whether coating treatment reduces friction and enhances the wear resistance of the fibers.
[0116] In this embodiment, through comprehensive analysis of the surface morphology and microporous structure of nylon staple fibers, combined with the results of mechanical properties tests and hygroscopicity tests, the comprehensive contribution of the surface morphology and microporous structure of nylon staple fibers in enhancing air permeability and toughness is further verified, ensuring that the fibers meet the design requirements of high-performance applications.
[0117] In this embodiment, the surface loss and deformation are measured in step 4, specifically including:
[0118] Obtain the mass data of the nylon staple fiber samples before and after the friction test, and calculate the mass loss rate based on the initial mass and the mass after friction;
[0119] Scan the surface of nylon staple fiber through an electron microscope, record the surface morphology data of nylon staple fiber sample before and after friction, and at the same time, record the depth, width and distribution characteristics of damage marks;
[0120] The depth deformation, width expansion and surface roughness change of the friction area of nylon staple fiber samples were measured, and the deformation degree of the samples was analyzed by combining the three-dimensional surface profile map. The ratio of the deformation loss area to the initial surface area was calculated to quantify the surface deformation loss rate.
[0121] Compare the damage morphology under different friction conditions, analyze the wear resistance of the nylon staple fiber surface coating, detect surface cracks, shedding and other damage characteristics, and evaluate the impact of friction on the durability of nylon staple fibers;
[0122] According to the loss test results under different friction conditions, the relationship curve between friction loss rate and friction times was drawn to analyze the time series change of short fiber loss rate;
[0123] If the test finds that the loss rate of the short fiber sample during the friction process exceeds the preset rate threshold, the friction and wear tester will trigger an abnormal alarm, analyze the microscopic characteristics of the abnormal loss area (such as breakage, shedding, etc.), and combine the scanning data to confirm the cause of the fault, such as the shedding of the fiber coating or the exposure of internal defects in the fiber.
[0124] In this embodiment, by obtaining the mass data before and after the friction test, calculating the mass loss rate, and combining with electron microscope scanning analysis, the surface morphology changes of the nylon staple fiber samples are comprehensively recorded, thereby quantifying the surface loss and deformation degree. It can not only accurately measure the depth deformation, width expansion and surface roughness change of the nylon staple fiber, but also analyze the deformation loss rate through the three-dimensional surface profile map, thereby effectively evaluating the durability of the nylon staple fiber.
[0125] In this embodiment, by comparing the damage morphology under different friction conditions, the wear resistance of the coating is analyzed, and a curve showing the relationship between the friction loss rate and the number of frictions is drawn. Combined with timely alarms for abnormal losses and microscopic feature analysis, it helps to quickly locate the cause of the fault, thereby improving product quality and reliability, significantly improving the wear resistance of nylon staple fiber products, extending their service life, enhancing the market competitiveness of the products, and providing consumers with higher quality textiles.
[0126] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high-tenacity breathable nylon staple fiber, comprising a core layer (1) and a sheath layer (2), characterized in that: The sheath layer (2) wraps the core layer (1) inside thereof, and the sheath layer (2) is provided with through holes (21) evenly distributed along the radial direction. The core layer (1) and the sheath layer (2) are bonded via an interface bulking agent to form a core-sheath bonding interface (3). The cross section of the nylon staple fiber is a hollow multi-lobed structure, the hollow rate of the hollow multi-lobed structure is 10%-30%, and the number of multi-lobed leaves is 8.
2. A high-tenacity breathable nylon staple fiber as claimed in claim 1, characterized in that: The nylon staple fibers are prepared by high-speed spinning and high-speed stretching deformation processes, wherein the spinning speed is not less than 4000 m / min, the stretching ratio is 1:3-1:5, the heat setting temperature is controlled within the range of 180°C-220°C, and the prepared fiber surface is coated and smoothed to obtain high-toughness breathable nylon staple fibers.
3. A high-tenacity breathable nylon staple fiber as claimed in claim 2, characterized in that: The obtained high-toughness breathable nylon staple fiber has a tensile strength greater than 6.0 cN / dtex; an elongation at break of 20%-40%; and an air permeability of not less than 20m 3 / h·m 2 , hygroscopicity is 4%-8%.
4. A testing process for high-tenacity breathable nylon staple fiber, applied to a high-tenacity breathable nylon staple fiber as claimed in claim 3, characterized in that: The following steps are involved: Step 1: Performance test: Perform a tensile test on the nylon staple fiber to measure its breaking strength and elongation, use an air permeability tester to measure the air permeability of the nylon staple fiber, and use a moisture vapor transmission rate tester to test the moisture permeability of the nylon staple fiber; Step 2: Surface structure analysis: Scan and observe the surface structure of nylon staple fibers, analyze the surface morphology and microstructure of nylon staple fibers, and verify the air permeability and structural characteristics of nylon staple fibers that enhance their toughness; Step 3: Fiber fineness measurement: Measure the fineness of the nylon staple fiber, weigh and calculate the diameter and surface characteristics of the nylon staple fiber to ensure that the diameter of the nylon staple fiber is within the range of 1-10μm; Step 4: Wear resistance test: The wear resistance of the staple fiber is tested based on a friction and wear tester. The staple fiber sample is rubbed with a specific material, the surface loss and deformation are measured, and the durability and long-term effectiveness of the nylon staple fiber in practical applications are evaluated.
5. A testing process for high-tenacity breathable nylon staple fibers as claimed in claim 4, characterized in that: The performance test specifically includes: Mechanical properties test: Ten nylon staple fibers were randomly selected from the same batch of high-tenacity breathable nylon staple fibers as test samples. The tensile strength of each test sample was tested using an electronic single-fiber tensile machine to determine the maximum tensile force and tensile breaking point of the test sample. The tensile modulus and elongation at break of the test sample are calculated based on the maximum tensile force and tensile breaking point, and the tensile properties of nylon staple fibers are evaluated by comparing the calculated results with the predetermined mechanical properties. Among them, the stretching speed of the electronic single fiber stretching machine is 500mm / min, the test temperature is 23℃, and the relative humidity is 65%; Air permeability test: The nylon staple fiber samples were pressed into fiber layers according to the specified thickness and density, and the air flow through the fiber layers was measured using an air permeability tester. The air permeability of the nylon staple fiber samples was evaluated based on the measurement results. The air permeability tester measures the amount of gas passing through the nylon staple fiber sample within a certain period of time under a constant airflow, and the unit of gas volume is m 3 / h*m 2 .
6. A testing process for high-tenacity breathable nylon staple fibers as claimed in claim 5, characterized in that: The air permeability test also includes: Moisture vapor transmission rate test: Under constant temperature and humidity conditions, place the nylon staple fiber sample in a dryer and record the initial mass of the nylon staple fiber sample; Expose the nylon staple fiber sample to an environment with a relative humidity of 65% for 12 hours, and record the mass of the nylon staple fiber sample after moisture absorption; The moisture absorption rate was calculated based on the initial mass and the mass after moisture absorption, that is, the moisture absorption was the percentage of the difference between the mass after moisture absorption and the initial mass. At the same time, the speed at which water vapor permeated through the nylon staple fiber sample was tested; The suitability of nylon staple fiber samples was evaluated based on the moisture absorption rate and the speed at which water vapor permeates through the nylon staple fiber samples.
7. A testing process for high-tenacity breathable nylon staple fibers as claimed in claim 6, characterized in that: The surface structure analysis comprises: Microscopic morphology analysis: Scanning the surface of the nylon staple fiber with an electron microscope to observe the microporous structure distribution, pore morphology and cross-sectional characteristics of the core-sheath bonding interface (3) on the surface of the nylon staple fiber; Verify the uniformity and microscopic bonding strength of the core-sheath bonding interface (3), analyze the number, distribution pattern and hollow ratio of the leaves in the hollow multi-leaf structure, and confirm whether the nylon staple fiber meets the design requirements; Micropore Characterization Evaluation: Determine the specific surface area and porosity of nylon staple fibers, record the pore size range and distribution frequency of the microporous structure, and verify whether the microporous structure is within the range of 1-10nm; The total amount of microporous structure was counted, and based on the statistical results and the fiber cross-sectional morphology, the contribution of the microporous structure to the air permeability was evaluated.
8. A testing process for high-tenacity breathable nylon staple fibers as claimed in claim 7, characterized in that: The surface structure analysis further includes: Surface energy determination: Based on the contact angle test method, the contact angle of water droplets on the surface of nylon staple fibers was measured, the surface energy parameters were calculated, and the polar component and dispersion component of the surface energy were decomposed; The dynamic changes of surface energy of nylon staple fibers treated with hydrophilic modifiers were analyzed to evaluate the modification effect of hydrophilic modifiers on surface hygroscopicity. Test the effect of different temperature and humidity conditions on the moisture absorption performance of the fiber surface, and evaluate the ability of nylon staple fibers to maintain hydrophilicity in long-term use environments; Combined with the surface energy parameters, verify whether the nylon staple fiber meets the technical requirements for enhanced moisture permeability and moisture absorption, and record the uniformity of the modifier distribution and the depth of action; Coating distribution analysis: Conduct layered observations on nylon staple fiber coatings, analyze the consistency of coating thickness and fiber surface coverage, and verify the adhesion performance of hydrophilic coating materials; Observe the microstructure of the nylon staple fiber coating, use microscope imaging technology to confirm whether the coating completely covers the fiber surface, and record the compatibility of the coating with the microporous structure; Test the adhesion of coating materials, evaluate the durability of coatings through multiple friction tests, and record the coating shedding rate and surface wear; The effect of coating on the surface friction coefficient of nylon staple fibers was analyzed to verify whether coating treatment reduces friction and enhances the wear resistance of the fibers.
9. A testing process for high-tenacity breathable nylon staple fibers as claimed in claim 8, characterized in that: The surface loss and deformation are measured in step 4, specifically including: Obtain the mass data of the nylon staple fiber samples before and after the friction test, and calculate the mass loss rate based on the initial mass and the mass after friction; Scan the surface of nylon staple fiber through an electron microscope, record the surface morphology data of nylon staple fiber sample before and after friction, and at the same time, record the depth, width and distribution characteristics of damage marks; The depth deformation, width expansion and surface roughness change of the friction area of nylon staple fiber samples were measured, and the deformation degree of the samples was analyzed by combining the three-dimensional surface profile map. The ratio of the deformation loss area to the initial surface area was calculated to quantify the surface deformation loss rate. Compare the damage morphology under different friction conditions, analyze the wear resistance of the nylon staple fiber surface coating, detect surface cracks, shedding and other damage characteristics, and evaluate the impact of friction on the durability of nylon staple fibers; According to the loss test results under different friction conditions, the relationship curve between friction loss rate and friction times was drawn to analyze the time series change of short fiber loss rate; If the test finds that the loss rate of the short fiber sample during the friction process exceeds the preset rate threshold, the friction and wear tester will trigger an abnormal alarm, analyze the microscopic characteristics of the abnormal loss area, and confirm the cause of the fault in combination with the scanning data.
10. A testing process for high-tenacity breathable nylon staple fibers as claimed in claim 9, characterized in that: It also includes comprehensive analysis and evaluation of test data, including: Based on the time series data of each test result, the performance characteristic curve of nylon staple fiber is drawn, and the time series change trend of mechanical properties, air permeability and wear resistance of nylon staple fiber is analyzed; Combine the performance characteristic curve data to conduct multi-dimensional evaluation of various test indicators, and extract key characteristic parameters based on the evaluation results; Calculate the comprehensive evaluation score of each test indicator according to the preset weight formula based on the test results; The tensile strength, elongation at break, air permeability, moisture permeability and abrasion resistance scores are weighted and summed to obtain the overall performance evaluation score of nylon staple fiber; Judging whether the nylon staple fiber meets the requirements of high toughness and air permeability indexes according to the overall performance score of the nylon staple fiber; If the evaluation result is lower than the preset standard, optimization suggestions will be output and improvements and adjustments will be made to the corresponding performance indicators. If the evaluation result meets the preset standard, testing and certification will be passed to confirm that the nylon staple fiber is suitable for the field of high-performance textiles.
Citation Information
Patent Citations
Functional polyamide fibre short -staple
CN207825612U